Influence of Organizational Excellence Factors on the Organizational Performance and Moderation of Organizational Support in Dubai Police - Fakhari, Nasser Yousuf Mohammad; Din, Badariah Haji; Romle, Abd. Rahim Bin (South Asian Journal of Social Sciences and Humanities, 2021)
This study is exploring the influences from different organisational excellence factors on the organisational performance besides to examination of the organisational support moderation interact in Dubai police in the UAE. The proposed model of this study is a combination between three organisational excellence factors, management support, and organisational performance. Innovation, personal commitment, and customer focus are the independent variables that have impact on the organisational performance as the dependent variable. Besides, management support is considered as the moderating variable in the particular model of this study. The actual sample of this research is 388 police officers, which was collected from different police stations and department in Emirate of Dubai.  The target or study population chosen for this research is the total number of police officers in all levels and all departments at the Dubai police. Overall, direct relationships for the seven predictors of organisational excellence factors are significant; the precedence for the relations based on the path coefficient value are personal commitment (0.750), innovation (0.683), and customer focus (0.631). For the moderating relationships of management support, it has no significant change in the path coefficient and the moderating effect is not significant.
Keywords: Management Support; Organisational Performance; Organisational Excellence; Innovation; Customer Focus; Personal Commitment